IMPACT TECHNOLOGICAL CAPITAL ON FINANCIAL DISTRESS - Pane, Zulfikar Ikhsan; Wangsih, Ingka Chintya (Klabat Accounting Review, 2024)
The growth of the transportation and logistics sector in Indonesia since 2017 has not been significant until now coupled with the ongoing Covid-19 pandemic which forced companies to adapt to health emergencies through adaptation to technology. This study examines adaptation to technology through the variable of technological capital disclosure to financial distress. Using 92 valid observations in transportation and logistics sector companies, it was concluded that technological capital disclosure has a significant negative effect on financial distress, meaning that the higher the technology adaptation, the more the company has the potential to experience financial distress because the adaptation requires costs plus the research period involving the Covid-19 pandemic. Keywords: technology, distress, disclosure Pertumbuhan sektor transportasi dan logistik di Indonesia sejak 2017 belum signifikan hingga saat ini ditambah berlangsungnya pandemi Covid-19 yang memaksa perusahaan untuk beradaptasi dengan kondisi kedaruratan kesehatan melalui adaptasi terhadap teknologi. Penelitian ini mengkaji adaptasi terhadap teknologi melalui variabel technological capital disclosure terhadap kesulitan keuangan. Menggunakan 92 observasi valid di perusahan sektor transportasi dan logistik diperoleh kesimpulan technological capital disclosure berpengaruh negatif signifikan terhadap kesulitan keuangan, artinya semakin tinggi adaptasi teknologi maka perusahaan berpotensi mengalami kesulitan keuangan karena adaptasi tersebut membutuhkan biaya ditambah periode penelitian melibatkan pandemi Covid-19. Kata Kunci: teknologi, kesulitan, pengungkapan